THE ROLE OF THE COURT OF MINISTERS OF THE REPUBLIC OF UZBEKISTAN IN COORDINATING THE ACTIVITIES OF STATE ADMINISTRATIVE BODIES (Web of Technology: Multidimensional Research Journal, 2024)
The article talks about the role of the Cabinet of Ministers of the Republic of Uzbekistan in coordinating the activities of state administration bodies.